Analysis of the deterioration process of the dolomite with the interlayer in different directions during wetting - Dai, Zhangjun; Wang, Yinhui; Zhou, Zhe; Li, Jian; Yu, Fei; Chen, Shanxiong (Frontiers in Materials, 2022)
Taking the dolomite with anhydrite interlayer at the bottom of Huangcaoshan Tunnel in Shanghai-Wuhan-Chengdu high-speed railway as the research object, the wetting deterioration and uniaxial compression tests were performed to study the influence of different interlayer orientations on the hygroscopic deterioration characteristics of rock and to analyze the process of rock deterioration. The wetting cracking and deformation characteristics of dolomite with interlayer in different directions were analyzed respectively from the time effect of rock micro-expansion and the change of ultrasonic longitudinal wave velocity, and the uniaxial compression evolution process of samples with different moisture absorption conditions and interlayer directions was analyzed respectively from the aspects of fracture volume strain and energy dissipation. The results show that the direction of interlayer had a significant effect on the wetting and deterioration of the rock. The sample with vertical interlayer cracked obviously during wetting, resulting in volume expansion along the axial and radial directions of the sample; However, the sample with horizontal interlayer had almost only axial volume expansion, and the expansion rate was small. After the rock was wet and deteriorated, the propagation velocity of ultrasonic longitudinal wave in the rock decreased, and the decrease amplitude in the sample with vertical interlayer was greater than that in the sample with horizontal interlayer. After rock wetting, its uniaxial compressive strength, crack initiation level, expansion level, and the threshold value of elastic strain energy density for failure decreased, while the radial peak strain, the energy conversion rate of dissipation increased, and the plastic characteristics of the sample were enhanced, and the sample with vertical interlayer changed significantly compared with the sample with horizontal interlayer.